Peopled Landscapes: Archaeological and Biogeographic Approaches to Landscapes (Terra Australis, 2012)
This impressive collection celebrates the work of Peter Kershaw, a key figure in the field of Australian palaeoenvironmental reconstruction. Over almost half a century his research helped reconceptualize ecology in Australia, creating a detailed understanding of environmental change in the Late Pleistocene and Holocene. Within a biogeographic framework one of his exceptional contributions was to explore the ways that Aboriginal people may have modified the landscape through the effects of anthropogenic burning. These ideas have had significant impacts on thinking within the fields of geomorphology, biogeography, archaeology, anthropology and history. Papers presented here continue to explore the dynamism of landscape change in Australia and the contribution of humans to those transformations. The volume is structured in two sections. The first examines evidence for human engagement with landscape, focusing on Australia and Papua New Guinea but also dealing with the human/environmental histories of Europe and Asia. The second section contains papers that examine palaeoecology and present some of the latest research into environmental change in Australia and New Zealand. Individually these papers, written by many of Australia's prominent researchers in these fields, are significant contributions to our knowledge of Quaternary landscapes and human land use. But Peopled Landscapes also signifies the disciplinary entanglement that is archaeological and biogeographic research in this region, with archaeologists and environmental scientists contributing to both studies of human land use and palaeoecology. Peopled Landscapes reveals the interdisciplinary richness of Quaternary research in the Australasian region as well as the complexity and richness of the entangled environmental and human pasts of these lands. - Prof. Peter Hiscock, The Australian National University